PENGARUH PROGRAM CORPORATE SOCIAL RESPONSIBILITY PT ANEKA TAMBANG TERHADAP PENINGKATAN TARAF HIDUP MASYARAKAT KECAMATAN NANGGUNG KABUPATEN BOGOR - Dwi Gemina (Fakultas Ekonomi Universitas Djuanda, 2015)
The purpose of the research is to determine the effect of corporate social responsibility program of PT Aneka Tambang to upgrade on community improvement Kecamatan Nanggung. Questioner distributed to 100 respondents. The questioner validity and reliability testing and test the classic assumption. Likert scale is used prior to testing with multiple regressions. The results of the study of corporate social responsibility program of PT Aneka Tambang in the fields of education, health, the environment, the increase in the basic human desires and needs as well as security simultaneously have an influence on the socio-economic communities. Partially, education, environment and safety effect on improving standards of living. While health, desires and basic needs no effect on improving standards of living.Keywords: Corporate Social Responsibility Program, Community Living Standard Improvement.